Dicrostonyx rubricatus - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Dicrostonyx rubricatus (Richardson, 1889). Zool. Capt. Beechey's Voy., p. 7. TYPE LOCALITY: USA, Alaska, Bering Strait. DISTRIBUTION: N Alaska, USA. SYNONYMS: alascensis. Published as part of Guy G. Musser & Michael D. Carleton, 1993, Order Rodentia - Family Muridae, pp. 501-755 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 511, DOI: 10.5281/zenodo.7353098